Records of Puma concolor in the Carcarañá basin, south of the Province of Santa Fe, Argentina - Rimoldi, Pablo Guillermo (2014)
Nine records of Puma concolor from southern Santa Fe Province (Argentina) are reported in the present contribution, being its relationships to environmental variables analyzed. The study area is located at the Carcarañá basin of the Pampean region, one the most modified wild ecosystems of the world. Among the four environmental units sampled, Puma concolor was reported at the halophilic communities of espartillar. Its presence could be indicative of a reoccupying process of areas where the species would have previously disappeared. The relative species abundance was of 0.37 traits per km. Concerning the environmental variables analyzed, it can be remarked that all the records have been related to water bodies in areas dominated by Spartina spartinae and at long distances from important routes and cities. This fact seems to be related to the pressure that the urbanization have on the species.